2018
DOI: 10.1038/s41598-018-19949-z
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis: Association between MGMT hypermethylation and the clinicopathological characteristics of non-small-cell lung carcinoma

Abstract: The relationship between O-6-methylguanine-DNA methyltransferase (MGMT) promoter methylation and clinicopathological characteristics of non-small-cell lung carcinoma (NSCLC) has remained controversial and unclear. Therefore, in this study we have undertaken a systematic review and meta-analysis of relevant studies to quantitatively investigate this association. We identified 30 eligible studies investigating 2714 NSCLC patients. The relationship between MGMT hypermethylation and NSCLC was identified based on 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…appears also in other human cancers such as cervical cancer [167], lung cancer [168], and glioblastoma [169].…”
Section: Interplay Of Dna Repair Pathwaysmentioning
confidence: 97%
See 1 more Smart Citation
“…appears also in other human cancers such as cervical cancer [167], lung cancer [168], and glioblastoma [169].…”
Section: Interplay Of Dna Repair Pathwaysmentioning
confidence: 97%
“…Meta-analysis of 10 studies comprising 910 ovarian tissue samples by Qiao et al concluded that the inactivation of MGMT might be associated with carcinogenesis in specific histological types of EOC [26]. Aberrant MGMT promoter methylation appears also in other human cancers such as cervical cancer [167], lung cancer [168], and glioblastoma [169].…”
Section: Direct Repairmentioning
confidence: 99%
“…TMZ is an alkylating agent prodrug, and its effect on tumor cells is to methylate the O6 residues of guanine preventing DNA duplication during cell proliferation and inducing cell death and apoptosis [ 95 ]. However, the DNA repair enzyme O-6-methylguanine-DNA methyltransferase (MGMT) is able to reverse the effects of alkylating agents as TMZ [ 96 98 ]. The MGMT promoter methylation is directly related to patient’s prognosis, as low promoter methylation status induces a high MGMT expression and a shorter survival due to a remarkable chemoresistance.…”
Section: Introductionmentioning
confidence: 99%
“…MGMT may play a very important role in carcinogenesis and invasive risk. It has been shown that MGMT hypermethylation is associated with an increased risk of NSCLC [8]. MGMT promoter methylation is also associated with the occurrence and invasion of melanoma [9].…”
Section: Discussionmentioning
confidence: 99%
“…O 6 -methylguanine-DNA methyltransferase (MGMT) is a widely studied specific DNA damage reversal repair protein that protects chromosomes from mutation, carcinogenesis, and cytotoxic effects of alkylating agents [7]. In previous studies, MGMT status was shown to be related to the occurrence and invasion of non-small cell lung cancer (NSCLC) [8], melanoma [9], malignant glioma [10], esophageal cancer [11], and prostate cancer [12]. MGMT also affected the chemotherapeutic effect of different tumor patients, but the results are controversial [8,9,13].…”
Section: Introductionmentioning
confidence: 99%